Investigation of water injection benefits on downsized boosted direct injection spark ignition engine. (15th March 2020) - Zhuang, Yuan; Sun, Yu; Huang, Yuhan; Teng, Qin; He, Bo; Chen, Wei; Qian, Yejian
Highlights: Water injection prolonged the combustion duration and decreased the index related to engine knock. Advancing spark timing ameliorated the negative impact of water injection on combustion and enabled high efficiency. Water injection reduced CO and NOx emissions while HC emissions increased. Abstract: Engine downsizing and boosting are key technologies to achieve the increasingly stringent emissions standards for spark ignition (SI) engines. However, knock is a major obstacle inhibiting further downsizing of SI engines. Water injection is a promising technology that has regained attention recently to solve the knock problem. In this paper, a 1.5L turbocharged gasoline direct injection (GDI) engine was modified by installing a water port injection (WPI) system on the intake manifold. The WPI system was modified from a GDI system and deionized water was pressured to 50 bar in a water tank by compressed nitrogen. The effect of WPI on engine combustion and emissions performance were experimentally investigated under different water/gasoline volume percentages and WPI timings. The results show that WPI has great potential in suppressing engine knock. At original engine setting (without adjustment of spark timing), all the combustion indexes related to knock are decreased by WPI, including maximum in-cylinder pressure (Pmax ) and maximum pressure rise rate (Rmax ). The flame kernel formation process (CA0-5), initiation combustion duration (CA0-10), early combustion duration (CA0-50) and major combustion duration (CA0-90) are deteriorated, resulting in decreased indicated mean effective pressure (IMEP) and thermal efficiency. By properly advancing spark timing, the combustion process can be improved, allowing the engine to achieve higher Pmax and better combustion phases without occurrence of knock. It is also found that the water/gasoline volume percentage should be kept within a proper range (30% in this study) because over WPI can lead to deterioration of combustion and pollutant emissions. WPI can effectively reduce the production of NO and CO emissions, while HC emissions are increased with the rise of water/gasoline volume percentage.